2018
DOI: 10.1186/s12991-018-0188-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of postpartum depression and interventions utilized for its management

Abstract: IntroductionPostpartum depression is a mood disorder that affects approximately 10–15% of adult mothers yearly. This study sought to determine the prevalence of postpartum depression and interventions utilized for its management in a Health facility in Ghana.MethodsA descriptive cross-sectional study design using a quantitative approach was used for the study. The study population included mothers and healthcare workers. Simple random sampling technique was used to select 257 mothers, while a convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
128
4
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(151 citation statements)
references
References 22 publications
8
128
4
11
Order By: Relevance
“…Symptoms associated with depression are extremely common following childbirth (1), with a considerable number of postpartum patients being diagnosed with clinically signi cant depression (2).…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms associated with depression are extremely common following childbirth (1), with a considerable number of postpartum patients being diagnosed with clinically signi cant depression (2).…”
Section: Introductionmentioning
confidence: 99%
“…PPD after childbirth is one of the complications that may affect mothers' in postpartum period. PPD is a mood disorder which affects approximately 10 to15 percent of adult mothers yearly [2]. PPD can also deteriorate mother-infant relationship and affect all aspects of mother's life including her social activities, personal functioning, and housekeeping ability.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple earlier studies also reported that good interpersonal relationships across the social support networks increase exibility to stress and subsidize enormously women from developing postpartum depression (78)(79)(80)(81) hence decreasing the risk of Postpartum depression. A study in Ghana on interventions for women with postpartum depression revealed that psychosocial support interventions are the most effective treatments implying an underling psychosocial de cit in this target population (82).…”
Section: Discussionmentioning
confidence: 99%